AN ANALYSIS OF HOW PEOPLE LEARN AT THE PLACE OF WORK - Karen Cacciattolo (European Scientific Journal, ESJ, 2015)
The paper analyses how people learn and illustrates the definition and meaning of learning and workplace learning, in which the theory of Lave and Wenger (1991) is analysed, including the strengths and limitations of the concepts of ‘communities of practice’ and ‘legitimate peripheral participation’. The paper contains the analysis and discussion of the inductively surfaced categories relating to workplace learning, which surfaced from the observations and interviews, as part of a study carried out at the University of Malta. The Analysis Section is mainly designed around four main categories which surfaced from the reading, coding and analysis of the data. These categories deal with the types of workplace learning, the most important part/s of the participants’ job, the ease of learning the relevant task/s and the feedback that the employees receive. Each category is supported by representative quotations from the fieldwork and the participants, and a few prominent issues regarding the categories are analysed and discussed in detail. The importance of learning by experience and informal learning is highlighted and issues of power and politics emerge throughout the discussion presented in the paper.